Performance of BLRI developed native duck under farmers condition with supplementary feeding (Bangladesh Journal of Livestock Research, 2016)
A total of 198 straight run day old ducklings of Bangladesh Livestock Research Institute (BLRI) developed native duck (named as Rupali and Nageswary) and local native duck genotypes were distributed among nine farmers of low laying areas of Kalihati Upazilla of Tangail district. Rupali and Nageswary ducklings were obtained from existing stock of BLRI and local native ducklings were collected from local farmers of the study area. After 12 weeks of age each farmers retained 10 female and 2 male ducks and sold away remaining ducklings. Farmers were instructed to supply 50g of balanced feed to their ducks in the morning and evening. Ducks were allowed to scavenge in the beel throughout the day. Data on: growth, feed intake, age at onset of lay, egg production rate, egg weight, mortality rate were recorded and cost-benefit was calculated. There found no significant difference on growth parameters, live weight gain, age at first laying or age at peak egg production among the duck genotypes. In the study highest live weight gain was found in Nageswary (1090 g) followed by Rupali (1058 g) and local native (912 g) duck at 8 weeks of age. Egg production rate of local native ducks (37.21%) was found significantly lower (P